TINGKAT STRES AKADEMIK SELAMA PANDEMI COVID-19 SISWA SD NEGERI SRIDADI 04 KECAMATAN SIRAMPOG KABUPATEN BREBES - Puji Lestari, Erna; Yusufi, Adnan (Jurnal Tawadhu, 2021)
During the pandemic, learning is carried out with a limited online and face-to-face system. This learning has the potential to cause academic stress in students, so the purpose of this study is to find out whether there is academic stress during the pandemic in students and what causes and efforts to overcome academic stress during the pandemic that occurred in fifth grade students at SD Sridadi Negeri 04 Sirampog. This study uses a qualitative research type with a descriptive percentage approach. Data collection techniques used are observation, questionnaires, interviews, and documentation. Based on the results of research that has been carried out, it shows that students experience moderate levels of academic stress covering aspects of physical, cognitive, emotional and social behavior. Factors causing academic stress in fifth grade students include internal factors (lack of interest in student learning, slow understanding and lack of memory of students on the material that has been studied) and external factors (lack of teacher professionalism, incomplete learning facilities in the school environment and at students' homes, too many assignments, lack of learning assistance from people parents and teachers). Efforts were made to overcome academic stress in Class V students, namely students taking lessons after school, the teacher reviewing the material on the questions.